Ace Your Self-Study: A Mobile Application to Support Self-Regulated Learning - Baars, Martine; Zafar, Farshida; Hrehovcsik, Micah; de Jongh, Edwin; Paas, Fred (Frontiers in Psychology, 2022)
Without guidance, students typically overestimate their understanding and memory of learning materials, which can have detrimental effects on the learning process. However, most students do not receive guidance or instruction about how to study. Moreover, students are largely unaware of strategies to self-regulate their learning and study effectively. Research has shown that prompting both cognitive and metacognitive strategies is effective to support self-regulated learning (SRL). Therefore we developed a mobile application, the Ace Your Self-study app, to prompt both cognitive and metacognitive strategies to support learning processes. In this article a theoretical background, description of the app’s features and design choices are presented. Also, data from the application in presented to give provide an idea of how the app has been used.